What explains the increase in the labor income share in Malaysia? - Allen Ng; Tan Theng Theng; Tan Zhai Gen (Asian Development Bank Institute (ADBI), 2018)
Labor income shares have been falling in many advanced and emerging economies within the last few decades, partly as a result of a combination of impacts from technology and increased global integration. This in turn is associated with the relatively slow growth of wages, especially for medium-skilled workers, and the worsening of the income inequality in these economies. In contrast, Malaysia's labor income share has been increasing since 2005, together with a reduction in income inequality. We investigate this development by exploring the differences in trends of the labor income shares across different economic sectors and firm sizes and identifying factors that could explain the increase in the labor income share in Malaysia. We find that the increase is mainly due to the growing importance of more traditional service subsectors and SMEs in the economy. This in turn is associated with greater reliance on low-skilled foreign workers during this period. These findings have important policy implications for Malaysia, including the potential trade-off between driving labor productivity and fostering inclusiveness. This contrarian trend offers insights that could be relevant to the experiences of, and policy choices available to, other emerging economies facing deindustrialization.
Keywords: E25; J30; J61; O3; 330; labor income share; foreign workers; technology; deindustrialization